2016
DOI: 10.3390/ijms17122081
|View full text |Cite
|
Sign up to set email alerts
|

Antithymocyte Globulin Induces a Tolerogenic Phenotype in Human Dendritic Cells

Abstract: Antithymocyte globulin (ATG) is used in the prevention of graft-versus-host disease during allogeneic hematopoietic stem cell transplantation. It is generally accepted that ATG mediates its immunosuppressive effect primarily via depletion of T cells. Here, we analyzed the impact of ATG-Fresenius (now Grafalon®) on human monocyte-derived dendritic cells (DC). ATG induced a semi-mature phenotype in DC with significantly reduced expression of CD14, increased expression of HLA-DR, and intermediate expression of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…ATLG is a polyclonal serum exerting its activity by depleting various cells of the immune system, such as T and B lymphocytes, by several mechanisms, including complement mediated lysis, antibody-dependent cellmediated cytotoxicity, increasing apoptosis, modulation of the function of cells involved in the migration phase of inflammation, interference with dendritic cells feature, and function and induction of T-cell regulatory cells. 22,23 The number of lymphocytes might be crucial for the determination of the effectively active dose of ATLG, since these cells represent the major target of the drug. A pharmacokinetic or pharmacodynamic model suggests that the area under the curve of ATG is predictive of transplant outcome influencing the immune reconstitution, GVHD, and relapse probability.…”
Section: Discussionmentioning
confidence: 99%
“…ATLG is a polyclonal serum exerting its activity by depleting various cells of the immune system, such as T and B lymphocytes, by several mechanisms, including complement mediated lysis, antibody-dependent cellmediated cytotoxicity, increasing apoptosis, modulation of the function of cells involved in the migration phase of inflammation, interference with dendritic cells feature, and function and induction of T-cell regulatory cells. 22,23 The number of lymphocytes might be crucial for the determination of the effectively active dose of ATLG, since these cells represent the major target of the drug. A pharmacokinetic or pharmacodynamic model suggests that the area under the curve of ATG is predictive of transplant outcome influencing the immune reconstitution, GVHD, and relapse probability.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we reviewed the literature and identified CCR7, L-selectin and LFA-1 as targets of ATG on T cells. 4043 In our hands, we observed that each Ag was expressed on both T cells and MDSCs. To determine which of these shared Ags were also bound by ATG, we pretreated T cells and MDSCs with ATG and observed a decrease in LFA-1 binding.…”
Section: Discussionmentioning
confidence: 60%
“…This is interesting, because all three of the antigens are known targets of ATG on T cells. [40][41][42][43] It is possible that in contrast to LFA-1, ATG bound to antigenic epitopes on CCR7 and L-selectin that were distinct from the antigenic targets of the Abs used to detect these molecules. These epitope differences may explain why ATG pre-treatment did not affect subsequent CCR7 and L-selectin binding.…”
Section: Discussionmentioning
confidence: 99%
“…In their protocol, ATG was administrated only in the haplo-group. Indeed, it was described that ATG not only induced a tolerogenic phenotype in human DCs (163), but was also able to mediate a complementmediated lysis of DCs (164). In summary, these findings may explain the delay in DC recovery in the setting of the haplo-HCT using the GIAC protocol.…”
Section: Dendritic Cellsmentioning
confidence: 80%